JAMSESSIONS: A flexible methodology to generate synergies between theory and practice in design courses - Sánchez-Gómez, Juana María; Nebot-Gómez-de-Salazar, Nuria; García-Granja, M. J. (RU BOOKS, 2018)
In the context of the Architecture degree, there are numerous subjects with a theoretical-practical content in which the methodology used fails to make the relationship between the two evident to students, as reflected in some of the surveys carried out on students. In the case of the subject Urbanism III of the Higher Technical School of Architecture of Malaga, it was the demotivation detected in the students, during the development of the exercises according to the traditional seminar model, which made us propose the JAMSESSIONS as an agile methodological alternative. capable of encouraging and generating new synergies between the theoretical-practical contents. The JAMSESSIONS take place in two class sessions. In the first, the students, organized by groups, carry out a brief investigation, based on the case studies provided through web links. Subsequently, a summary document is generated that is made available to the rest of the classmates on the virtual campus. In the second session, said document is analyzed and submitted to critical debate and conclusions in small working groups. This dynamic allows: 1-Increase the attention and active participation of students as it is a brief and effective process. In addition to arousing their interest in continuing to investigate on their own. 2- Promote the selective and accurate use of the abundant database provided by the Internet and promote the use of the archive and open forum for debate, provided by the Virtual Campus of the University. 3-Recover the traditional dialectic taking advantage of the potential for intensity and spontaneity that is generated in a face-to-face encounter. This communication aims to delve into the methodology and the results obtained, with the intention of sparking a debate that will help us to implement it, once its effectiveness has been verified, for the numerous core subjects as a catalyst and dynamizer of the relationship between its theoretical-practical contents.
Capítulo del libro: Educational Innovation in Architecture & Engineering. Advances in final projects and thesis
Se adjunta archivo de autorización del editor para la publicación del capítulo en RIUMA
Keywords: Arquitectura - Estudio y enseñanza; Aprendizaje colaborativo; Enseñanza profesional - Metodología; Urbanismo - Programas de estudio; Universidad de Málaga Escuela Técnica Superior de Arquitectura; Jamsessions; Teaching innovation; Collaborative methodology; Theoretical-practical content; Urbanism; School of Architecture; Malaga